Trunk Control Balance and Upper Extremity Function in Ambulatory Children with Diplegic Cerebral Palsy: A Comparative Study - Ugur Tosun, Burcin; Gokalp, Ozge; Yilmaz Gokmen, Gulhan; Tuzun, Emine Handan (Karger, 2025)
Introduction: This study aimed to investigate trunk control, balance, and upper extremity skill quality in ambulatory children with diplegic cerebral palsy (CP) classified as Gross Motor Function Classification System (GMFCS)-I and -II, as well as to compare the GMFCS groups among themselves and with healthy children. Methods: Twenty-five children with spastic diplegic CP (11.80 +/- 2.66 years) and 30 healthy children (13.57 +/- 3.48 years) were included. Functional levels were classified with the GMFCS, with 13 children classified as GMFCS-I and 12 as GMFCS-II, while trunk control was assessed with the Trunk Control Measurement Scale (TCMS), balance with the Single-Leg Stance and Four-Square Step Tests, and upper extremity functionality with the Quality of Upper Extremity Skills Test (QUEST). Results: There was no significant difference in age, body mass index, or gender distribution between the CP and control groups (p > 0.05). The healthy group outperformed both CP groups in all clinical evaluations. No significant differences were found between GMFCS-I and GMFCS-II groups in the Single-Leg Stance Test, Four-Square Step Test, and QUEST parameters (p > 0.05). However, TCMS subdomains static sitting (p = 0.009), dynamic reaching (p = 0.018), selective movement control (p = 0.012), and total scores (p = 0.006) were significantly higher in the GMFCS-I group. A moderate positive correlation and a 54% regression rate were observed between the QUEST and TCMS scores. Conclusion: Trunk control is a key determinant of upper extremity skill quality in children with CP. Core stabilization should be prioritized to improve upper extremity functionality and manage disability levels effectively. 2025 The Author(s). Published by S. Karger AG, Basel
Keywords: Trunk control; Cerebral palsy; Children's balance; Functional upper extremity levels